Detection of major VOCs in exhaled breath under ppb level using porous ZnO nanobelts. Issue 2 (15th September 2022) - Kim, Kyusung; Choi, Pil gyu; Itoh, Toshio; Masuda, Yoshitake
Abstract: Atomic defects can enhance catalytic efficiency by providing coordinatively unsaturated sites in the crystal structure of metal oxides. It allows facile chemical reactions because the sites can react with other molecules with relatively lower energy. Therefore, atomic defect engineering can be a cost‐effective strategy to replace novel metal catalysts for the development of ultrasensitive gas sensors. Herein, we fabricated porous ZnO nanobelts with atomic step structures for acetone, ethanol, and isoprene gas sensing under the parts‐per‐billion (ppb) level. Numerous atomic step structures could be formed by removing H and F atoms during the conversion process of ZnOHF at 500°C. The synthesis method of metal oxide nanomaterial by conversion from metal hydroxide fluoride will provide the atomic defects and it will be useful to prepare ultrasensitive sensing material. Furthermore, the gas selectivity of the porous ZnO nanobelt was investigated based on the appearance energy associated with the separation of the methyl group.